ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI PADA KANTOR DPRD PROVINSI SUMATERA SELATAN - Vinkan Amanda Putri; Maliah Maliah (JURNAL KOMPETITIF, 2021)
This research aims to analyse the factors that affect the performance of employees in the DPRD office of South Sumatera Province, the factors in this research are limited to the motivation of work and work discipline towards employee performance. This method of study uses quantitative methods that are methods in the form of data and numbers with a descriptive approach that is to formulate and interpret the existing data and methods of collecting it by spreading the questionnaire (poll). The samples in this study were as much as 50 employees. The data analysis in this research is using SPSS program (Stasistical Product and Service Solution) version 23. The instrument testing techniques in the study covered the validity test and the reliability test and the hypothesis testing criteria is the T test and F test.Based on data management, it is obtained that the multiple linear regression equation is Y = 77.076 + 0.262X1 + (-0.684)X2 + e. Based on the hypothesis test with the t test, the results showed that partially work motivation had no significant effect on employee performance, while work discipline had a significant effect on employee performance. The results of the f test show that simultaneously work motivation and work discipline have an effect on employee performanceThis research aims to analyse the factors that affect the performance of employees in the DPRD office of South Sumatera Province, the factors in this research are limited to the motivation of work and work discipline towards employee performance. This method of study uses quantitative methods that are methods in the form of data and numbers with a descriptive approach that is to formulate and interpret the existing data and methods of collecting it by spreading the questionnaire (poll). The samples in this study were as much as 50 employees. The data analysis in this research is using SPSS program (Stasistical Product and Service Solution) version 23. The instrument testing techniques in the study covered the validity test and the reliability test and the hypothesis testing criteria is the T test and F test.Based on data management, it is obtained that the multiple linear regression equation is Y = 77.076 + 0.262X1 + (-0.684)X2 + e.Based on the hypothesis test with the t test, the results showed that partially work motivation had no significant effect on employee performance, while work discipline had a significant effect on employee performance. The results of the f test show that simultaneously work motivation and work discipline have an effect on employee performance